Design of SFRC members aided by a multiscale model: Part II – Predicting the behavior of RC-SFRC beams - Trindade, Yasmin T.; Bitencourt, Luís A.G.; Manzoli, Osvaldo L. [UNESP] (Elsevier, 2020)
In the preceding Part I of this study, an experimental program and numerical analyses using a multiscale model are performed to obtain the post-cracking parameters of steel fiber reinforced concrete (SFRC) through the simulation of three-point bending tests (3-PBT) according to EN 14651. In the present Part II, both numerical and experimental parameters obtained from the 3-PBT are used on the design of beams with combined reinforcement of steel fibers and rebars (RC-SFRC beams) according to fib Model Code 2010 in order to study their influence on the amount of bending and shear reinforcements required. In addition, the RC-SFRC beams designed are numerically simulated using the mesoscale model and the results are compared to the designed ones in terms of crack width, mean crack spacing, deflection and ultimate and service loads. The results demonstrated that computational simulations with an appropriated approach to represent the composite may be an important tool to contribute on the design of SFRC structural members.
Keywords: Experimental tests; fib Model Code; Numerical modeling; Post-cracking behavior; RC-SFRC beams; SFRC